On one bifurcation in relaxation systems - Kolesov, A. Yu.; Mishchenko, E. F.; Rozov, N. Kh. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We establish conditions under which, in three-dimensional relaxation systems of the form $$\dot{x} = f(x, y, μ),\quad, ε\dot{y} = g(x, y),\quad x= (x_1, x_2) \in {\mathbb R}^2,\quad y\in{\mathbb R },$$ where $0 < ε